Reoperation after coronary bypass grafting. - Menkis, A. H. (College of Family Physicians of Canada, 1993)
Coronary artery bypass grafting is one of the most commonly performed surgical procedures in the western world, and myocardial revascularization during the first operation is well established. But patients are now surviving beyond the patency of their primary grafts. Repeat myocardial revascularization can be performed successfully in patients who have adequate ventricular function and graftable distal vessels.